2022
DOI: 10.1108/tqm-03-2022-0081
|View full text |Cite
|
Sign up to set email alerts
|

Developing Internet of Things-related ISO 10001 Hand Hygiene Privacy Codes in healthcare

Abstract: PurposeAugmentation of an ISO 10001 code system for healthcare worker (HW) satisfaction with ISO/IEC 27701 and ISO/IEC 29184 privacy-related subsystems is shown. Four specific codes regarding the privacy of HWs using electronic devices for hand hygiene (HH) monitoring and the related activities are presented.Design/methodology/approachHWs’ concerns involving automated hand hygiene monitoring technologies were identified through a literature review and classified. Privacy codes (PCs) that deal with such concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…The contributions grouped in this cluster investigate the role that digitalization plays in (1) boosting learning activities for human capital development (Barile et al ., 2023), (2) improving the digital service quality process (Brunetti et al ., 2023), (3) detecting user satisfaction (Magno and Dossena, 2023), (4) service quality practices (Schiavone et al ., 2023), (5) increasing quality assurance of automated hand hygiene monitoring service through the ISO certifications (Ortiz and Karapetrovic, 2023) and (6) fostering antifragility in the context of small and medium-sized service companies (service SMEs) (Corvello et al ., 2023).…”
Section: Contributions In This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The contributions grouped in this cluster investigate the role that digitalization plays in (1) boosting learning activities for human capital development (Barile et al ., 2023), (2) improving the digital service quality process (Brunetti et al ., 2023), (3) detecting user satisfaction (Magno and Dossena, 2023), (4) service quality practices (Schiavone et al ., 2023), (5) increasing quality assurance of automated hand hygiene monitoring service through the ISO certifications (Ortiz and Karapetrovic, 2023) and (6) fostering antifragility in the context of small and medium-sized service companies (service SMEs) (Corvello et al ., 2023).…”
Section: Contributions In This Special Issuementioning
confidence: 99%
“…The study represents the first attempt to combine quality, services and digitalization, by providing a model that is able to identify the different levers of quality in digital-based services organizations. Ortiz and Karapetrovic (2023) proposed an integrated management system based on augmentative quality and privacy management standards to support the implementation of an IoT-based hand hygiene monitoring technology (HHMT). Based on a multi-layered methodology, the findings showed that the identification of an informed consent form is a critical resource for the fulfillment of privacy-related codes for healthcare workers satisfaction.…”
Section: Digital Transformationmentioning
confidence: 99%
“…There are also a great number of usual applications for the IoT, such as sensors in hospital rooms that may keep track of a patient's vital signs throughout the day to assist medical professionals with diagnosis and treatment. The widespread distribution of COVID-19 has accelerated the development of this technology [48], [55], [123], [125], [136], [149], [204], [253], [297], [304], [319], [330], [338]- [341].…”
Section: Iot Technology In Healthcarementioning
confidence: 99%